Analyzing the Influence of Viral Marketing and Product Quality on Purchasing Decisions for K-pop Merchandise - Chelsya; Hommy Dorthy Ellyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to examine and analyze the influence of Viral Marketing and Product Quality on Purchase Decisions regarding K-pop merchandise among students of SMA Swasta Mentari Bangsa Medan. The sample for this research consists of 16 respondents who have previously purchased K-pop merchandise. The analytical method employed in this study is quantitative, with data collected as primary data derived from respondents' answers to distributed questionnaires. The data processing method used is multiple linear regression analysis, employing SPSS version 23. The data collection method used is purposive sampling. The results of the partial hypothesis testing indicate that viral marketing does not have a positive and significant effect on purchase decisions, whereas product quality does have a positive and significant effect on purchase decisions. The results of the simultaneous hypothesis testing (F-test) demonstrate that both viral marketing and product quality influence purchase decisions, with an F-value of 17.630 and a significance value of 0.000. Therefore, based on the F-value (17.630) being greater than the critical F-value (3.74), the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, with a significance level (0.000) being less than alpha (0.005), indicating a very significant relationship due to the significance value (0.000).